2019
DOI: 10.1111/imb.12627
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of heat shock protein 70 genes by class I histone deacetylases in the red flour beetle, Tribolium castaneum

Abstract: The regulatory function of histone acetylation in the expression of genes encoding heat shock proteins (Hsps) has been documented in Drosophila melanogaster; however, knowledge of the role of acetylation in modulating Hsps in other insect pests is limited. In this study, two full‐length cDNAs encoding inducible Hsp70 (designated TcHsp70) and heat shock cognate 70 (TcHsc70) were isolated and characterized in the red flour beetle, Tribolium castaneum. TcHsp70 and TcHsc70 cDNAs were 2256 and 2132 bp and encoded 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…HSPs identified as differentially expressed in this study support past results for beetle species and other insects more broadly. A major trend in our results concerned the upregulation of HSP70 genes at high temperatures, particularly Hsp68 ; HSP70s are highly expressed in response to heat shock in other beetle species, including cave-adapted subterranean taxa 28 , 49 , 50 , and work in concert with sHSPs and HSP90s 51 – 54 . In addition to the heat shock proteins, we also observed the upregulation of the heat shock cognates Hsc70-3 and Hsc70-4 and putative cochaperones Samui , DnaJ , AHSA1 , and Unc45a at 35 °C relative to the 25 °C treatment.…”
Section: Discussionmentioning
confidence: 71%
“…HSPs identified as differentially expressed in this study support past results for beetle species and other insects more broadly. A major trend in our results concerned the upregulation of HSP70 genes at high temperatures, particularly Hsp68 ; HSP70s are highly expressed in response to heat shock in other beetle species, including cave-adapted subterranean taxa 28 , 49 , 50 , and work in concert with sHSPs and HSP90s 51 – 54 . In addition to the heat shock proteins, we also observed the upregulation of the heat shock cognates Hsc70-3 and Hsc70-4 and putative cochaperones Samui , DnaJ , AHSA1 , and Unc45a at 35 °C relative to the 25 °C treatment.…”
Section: Discussionmentioning
confidence: 71%
“…HSPs identified as differentially expressed in this study support past results from beetle species and other insects more broadly. A major trend from our results concerned the upregulation of HSP70 genes, particularly Hsp68 ; HSP70s are highly expressed in response to heat shock in the Colorado potato beetle (Yocum, 2001), red flour beetle (Chen et al, 2020), and the cave beetle Neobathyscia (Bernabò et al, 2011). These genes are upregulated in concert with sHSPs and HSP90 genes in the rice weevil (Yuan et al, 2014) and Japanese sawyer beetle (Cai et al, 2017) under the same conditions.…”
Section: Discussionmentioning
confidence: 77%
“…HSPs identified as differentially expressed in this study support past results for beetle species and other insects more broadly. A major trend in our results concerned the upregulation of HSP70 genes at high temperatures, particularly Hsp68; HSP70s are highly expressed in response to heat shock in other beetle species, including cave-adapted subterranean taxa (28,49,50), and work in concert with sHSPs and HSP90s (51)(52)(53)(54). In addition to the heat shock proteins, we also observed the upregulation of the heat shock cognates Hsc70-2, Hsc70-3, and Hsc70-4 and cochaperones Tsc2, Samui, DnaJ, AHSA1, Unc45a in at 35ºC relative to the 25ºC treatment.…”
Section: Heat Shock-induced Gene Expression In Parostermentioning
confidence: 76%
“…HSP70 is one of the critical predictors of insect tolerance to heat stress. Previous studies showed that higher induced levels of HSP corresponded to stronger heat tolerance in arthropods (Chang et al ., 2018; Chen et al ., 2020). MaltHSP70s accumulated by over a thousand-fold after heat shock, which implied that MaltHSP70s were more sensitive than HSP70s in other insects (Li et al ., 2009; Udaka et al ., 2010; Wang et al ., 2015; Quan et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%